A model for assessing and re‐assessing the value of software reuse. Issue 4 (4th October 2016) - Svahnberg, Mikael; Gorschek, Tony
Abstract: Background: Software reuse is often seen as a cost avoidance rather than a gained value. This results in a rather one‐sided debate where issues such a resource control, release schedule, quality, or reuse in more than one release are neglected. Aims: We propose a reuse value assessment framework, intended to provide a more nuanced view of the value and costs associated with different reuse candidates. Method: This framework is constructed based on findings from an interview study at a large software development company. Results: The framework considers the functionality, compliance to standards, provided quality, and provided support of a reuse candidate, thus enabling an informed comparison between different reuse candidates. Furthermore, the framework provides means for tracking the value of the reused asset throughout subsequent releases. Conclusions: The reuse value assessment framework is a tool to assist in the selection between different reuse candidates. The framework also provides a means to assess the current value of a reusable asset in a product, which can be used to indicate where maintenance efforts would increase the utilized potential of the reusable asset. Abstract : Reuse value assessment framework is a framework for assessing and comparing specific value influencing aspects of different reusable software assets. The framework not only enables an informed first reuse decision but also provides a means for re‐assessing the value based on updated needs and updated capabilities of the reused assets.